HIGHER SCHOOL TEACHING ENVIRONMENT (about the «patterns») - Valery P. Shestak (Moscow Polytechnic University, 2016)
The article continues the series of the author's publications on the topic of higher school ethos. The author considers the elite corps of professors to be an intellectual reserve of Russia. This paper proposes an option of choice of the actual pattern characteristics of higher school professors, which are considered within a multi-dimensional model of a professor; it includes the psychological hierarchy of needs, the national higher school modernization plans and examples of financial incentives.